The Trace of the Arabic Language on the Rest of the World's Languages (Journal of the College of Basic Education, 2026)
"The Trace of the Arabic Language on the Rest of the World's Languages"This research explores the deep and multifaceted influence of the Arabic language on various world languages. Far beyond its religious role, Arabic has served as a powerful cultural and linguistic force, shaping vocabularies, structures, and thought patterns in diverse regions across history.The study identifies five primary factors that facilitated the spread of Arabic: Islam, Islamic conquests, scientific and cultural achievements, trade, and geographic proximity. These factors helped embed Arabic not only lexically but also morphologically, phonetically, semantically, and syntactically in several languages, especially Persian, Turkish, Urdu, Swahili, and Spanish.;The research highlights how Arabic root patterns and morphological structures were adopted and adapted in recipient languages. It also sheds light on how religious terms and Islamic concepts were integrated unchanged, becoming foundational to the religious and legal discourse in these societies.During the Islamic Golden Age, Arabic's scientific prestige led to widespread translation efforts, which transferred thousands of Arabic terms and ideas into Latin and other European languages. The impact of Arabic persisted, forming the backbone of linguistic interaction in many Islamic communities, and remains visible today despite modern linguistic shifts.Ultimately, the research concludes that Arabic’s influence was not merely lexical but structural and philosophical—contributing deeply to the formation of thought and cultural identity in a wide array of linguistic systems.